Using Fable In Developing Reading Comprehension of Grade Eight Students of SMP Negeri 2 Balaesang - Alisa, Nur; Anggreni, Afrilia; R. Mertosono, Sudarkam (Jurnal Onoma: Pendidikan, Bahasa, dan Sastra, 2024)
The objective of this research is to find out if using fable can develop the reading comprehension of grade eight students of SMP Negeri 2 Balaesang. This research used a quasi-experimental research design. The population of this research was the grade eight students of SMP Negeri 2 Balaesang. The researchers was selected using the cluster sampling technique. The sample of this research were 54 students, which were divided into 27 the students of VIIIB as a experimental group and 27 the students of VIIIA as a control group. The data were collected through the reading test that consisted of pre-test and post-test. By applying the 0.05 level significance, the researchers found that the sig value obtained (p) was lower than alpha (α) (0,000<0,05) It means that the hypothesis is accepted or using fable can develop reading comprehension of grade eight students of SMP Negeri 2 Balaesang. This research implies that the use of fable can increase students' literacy, make learning more enjoyable, and boost their activeness and engagement in the learning process.